Causal pathways in lymphoid leukemia: the gut microbiota, immune cells, and serum metabolites - Zhuang, Xin; Yin, Qingning; Yang, Rong; Man, Xiaoying; Wang, Ruochen; Geng, Hui; Shi, Yifen (Frontiers in Immunology, 2024)
Background：We employed Mendelian randomization (MR) to investigate the causal relationship between the gut microbiota and lymphoid leukaemia, further exploring the causal relationships among immune cells, lymphoid leukaemia, and potential metabolic mediators. Methods：We utilized data from the largest genome-wide association studies to date, encompassing 418 species of gut microbiota, 713 types of immune cells, and 1,400 serum metabolites as exposures. Summary statistics for lymphoid leukaemia, acute lymphocytic leukaemia (ALL), and chronic lymphocytic leukaemia (CLL) were obtained from the FinnGen database. We performed bidirectional Mendelian analyses to explore the causal relationships among the gut microbiota, immune cells, serum metabolites, and lymphoid leukaemia. Additionally, we conducted a two-step mediation analysis to identify potential intermediary metabolites between immune cells and lymphoid leukaemia. Results：Several gut microbiota were found to have causal relationships with lymphoid leukaemia, ALL, and CLL, particularly within the Firmicutes and Bacteroidetes phyla. In the two-step MR analysis, various steroid hormone metabolites (such as DHEAS, pregnenolone sulfateprogestogen derivatives, and androstenediol-related compounds) were identified as potential intermediary metabolites between lymphoid leukaemia and immune cells. In ALL, the causal relationship between 1-palmitoyl-2-docosahexaenoyl-GPE (16:0/22:6) and ALL was mediated by CD62L-plasmacytoid DC%DC (mediated proportion=-2.84%, P=0.020). In CLL, the causal relationship between N6,n6,n6-trimethyllysine and CLL was mediated by HLA DR+ CD8br AC (mediated proportion=4.07%, P=0.021). Conclusion：This MR study provides evidence supporting specific causal relationships between the gut microbiota and lymphoid leukaemia, as well as between certain immune cells and lymphoid leukaemia with potential intermediary metabolites.